2010
DOI: 10.1080/07924259.2010.9652325
|View full text |Cite
|
Sign up to set email alerts
|

Reproductive cycle and fecundity ofPotimirim glabra(Kingsley, 1954) (Caridea, Atyidae) from a littoral stream

Abstract: The reproductive cycle of Potimirim glabra, especially the female size at sexual maturity, reproductive period and fecundity, was studied at two sites of one of the northern littoral streams in the state of São Paulo, Brazil. Prawns were collected monthly for one year. The minmum size at sexual maturity was estimated from the smallest ovigerous female (cephalothorax length = CL), and the reproductive period was determined monthly by examining the relative frequency of ovigerous females. Size comparisons betwee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
13
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 19 publications
(20 reference statements)
2
13
1
Order By: Relevance
“…Determination of the reproductive period was based on the temporal variation in the relative frequency of ovigerous females (Barros & Fontoura, 1996a;Bueno & Shimizu, 2008;Rocha et al, 2010). Minimum size at sexual maturity in females was based on the smallest ovigerous specimen sampled (Barros & Fontoura, 1996a;Lima & Oshiro, 2002;Martínez-Mayen & Román-Contreras, 2005;Hoffmann & Negreiros-Fransozo, 2010). Minimum size at sexual maturity in males could not be determined because all sampled males exhibited a fully developed appendix masculina on the second pleopod.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Determination of the reproductive period was based on the temporal variation in the relative frequency of ovigerous females (Barros & Fontoura, 1996a;Bueno & Shimizu, 2008;Rocha et al, 2010). Minimum size at sexual maturity in females was based on the smallest ovigerous specimen sampled (Barros & Fontoura, 1996a;Lima & Oshiro, 2002;Martínez-Mayen & Román-Contreras, 2005;Hoffmann & Negreiros-Fransozo, 2010). Minimum size at sexual maturity in males could not be determined because all sampled males exhibited a fully developed appendix masculina on the second pleopod.…”
Section: Methodsmentioning
confidence: 99%
“…The family Atyidae alone comprises approximately 470 species/subspecies of freshwater and anchialine shrimps that inhabit subtropical and tropical ecosystems (e.g., Guo & De Grave, 2004;De Grave et al, 2008;Hoffmann & Negreiros-Fransozo, 2010;De Grave & Fransen, 2011).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, we found that the second spawning period was longer than the first, and that more individuals were involved in the second spawning (i.e., in spawning group II). Oviposition in some decapods is known to be controlled not only by endogenous mechanisms but also by favourable environmental conditions (Hoffmann & Negreiros-Fransozo, 2010). Therefore, the second spawning period may be longer than the first because of increased temperatures at that time.…”
Section: Spawning Periodsmentioning
confidence: 99%
“…The reproductive period of caridean shrimps is characterized by the presence of ovigerous females, the frequency of which may vary during different seasons, indicating peaks of reproductive activity for each population, which are reflected in the gonadosomatic indices and larval hatching rates (Sanz, 1987;Hoffmann & Negreiros-Fransozo, 2010). In this study, we found that ovigerous females were present throughout the year, and that there were two main spawning periods, one in the fall to early winter, the other in the late winter to spring; this indicates that A. lar spawns at least twice during the year.…”
Section: Spawning Periodsmentioning
confidence: 99%